2019
DOI: 10.1186/s13104-019-4531-6
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality and its predictors among type 2 diabetes mellitus patients attending Jimma University Medical Center, Jimma, Ethiopia

Abstract: Objectives The aim of this study is to determine the prevalence of poor sleep quality and its associated factors among people with type 2 diabetes mellitus at Jimma University Medical Center, Jimma, Ethiopia 2018. Comparative cross-sectional study was employed on 198 participants (99 cases and 99 controls). Data were collected using Pittsburgh Sleep Quality Index (PSQI) and analyzed using SPSS version 20. Variables with p value ≤ 0.05 in multivariable logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 23 publications
7
38
1
1
Order By: Relevance
“…From the formula "n" denotes sample size, " α 2 " is the reliability coefficient of standard error at the 5% level of significance with z =1.96, "p" is proportion and "d" is level of standard error. The prevalence (p) used was 55.6%, which was taken from a previous study done in Ethiopia, 16 to determine the sample size of 379 and 10% non-response rate was taken to determine the total sample size of 417. The sample size of the second objective was calculated using STATCalc Epi info version 7 by taking a proportion of factors from a similar study conducted in Ethiopia.…”
Section: Sample Size Determination and Sampling Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…From the formula "n" denotes sample size, " α 2 " is the reliability coefficient of standard error at the 5% level of significance with z =1.96, "p" is proportion and "d" is level of standard error. The prevalence (p) used was 55.6%, which was taken from a previous study done in Ethiopia, 16 to determine the sample size of 379 and 10% non-response rate was taken to determine the total sample size of 417. The sample size of the second objective was calculated using STATCalc Epi info version 7 by taking a proportion of factors from a similar study conducted in Ethiopia.…”
Section: Sample Size Determination and Sampling Proceduresmentioning
confidence: 99%
“…23 Duration of diabetes mellitus: Duration of ≤ 10 years since the first diagnosis is considered short duration and > 10 years is considered to be long duration. 16 Poor glycemic control: The average fasting blood glucose on three consecutive visits is > 130 or less than 70 mg/dl. 24 Good glycemic control: A 3-month average fasting blood glucose was between 70 and 130.…”
Section: Operational Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies indicated that sleep deprivation and excessive sleep duration can exert an adverse effect on hormones, metabolism and immune function [ 3 – 5 ]. From epidemiological aspects, although dozens of studies reported that inappropriate sleep duration and poor sleep quality are reported to be associated with high risk of some common diseases, including diabetes [ 6 ], cardiovascular diseases [ 7 ] and cancer [ 8 ], as well as to increased all-cause and cause-specific mortality rates [ 9 ], these associations are not often reproducible.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests that sleep plays an important role in human mental and physical health [1,2]. Inappropriate sleep duration and poor sleep quality are closely related to common chronic diseases, including diabetes [3], cardiovascular diseases [4] and cancer [5], as well as increased all-cause and cause-specific mortality rates [6]. In addition, sleep deprivation and excessive sleep duration have adverse effects on hormone levels, metabolism and immune function [7][8][9].…”
Section: Introductionmentioning
confidence: 99%